The White Earth Nation : Ratification of a Native Democratic Constitution - Vizenor, Gerald (Book collections on Project MUSE., 2012)
The White Earth Nation of Anishinaabeg Natives ratified a new constitution in 2009, the first indigenous democratic constitution, on a reservation in Minnesota. Many Native constitutions were written by the federal government, and with little knowledge of the people and cultures. The White Earth Nation set out to create a constitution that reflected its own culture. The resulting document provides a clear Native perspective on sovereignty, independent governance, traditional leadership values, and the importance of individual and human rights. This volume includes the text of the Constitution o.